The unconventional myosin CRINKLED and its mammalian orthologue MYO7A regulate caspases in their signalling roles - Mariam H. Orme (Nature Portfolio, 2016)
In addition to their role in apoptosis, caspases are also involved in mediating non-apoptotic events. Here the authors show that the Drosophilamyosin family member CRINKLED and its mammalian counterpart act as substrate adaptor that facilitate caspase-mediated cleavage and localised kinase activity.